EFEK EKSTRAK BIJI JARAK PAGAR (Jatropha curcas L) TERHADAP REGULASI EKSPRESI GEN TGF-β1 SEBAGAI MARKER TUMOR - Endah Wulandari; Rr. Ayu Fitri Hapsari (Majalah Obat Tradisional, 2017)
The role of TGF-β1 is known as the main immunosuppresor associated with tumor, but on the other opinion, it is associated with proliferation and tumor invasion. The increase and decrease of the secretion of TGF-β is to regulate the proliferation, differentiation, and death of various cell types. Now we all know the extract of Jatropha curcas L seed serves as antitumor. Allegedly, it can regulate the expression of TGF-β1 in control of cell number. The purpose of this study is to determine the effects of Jatropha seeds to the regulation of gene expression of TGF-β1 as a tumor marker. The method is performed by giving a dose groups the extract of jatropha seed (0, 5, 25, 50, 250 mg/BB) in mice. Then measurement of mRNA expression (RT-PCR), the protein of TGF-β1 levels (ELISA), and qualitative observations of liver histology were done. The expression of TGF-β1 mRNA is significantly 4.39 to 7.34 times higher than (ANOVA, p 0.05) than the control. Histological observation of liver showed the extract of jatropha seed induces damage nucleus of hepatocytes cell and sinusoidal. The effects extract of jatropha seed increased the level of TGF-β1 mRNA but not followed by increasing protein of TGF-β1 levels, and it was stimulated necrosis and apoptosis of hepatocytes cell.